Association of 25-hydroxy vitamin D level with the blood pressure response to a maximum exercise test among professional indoor athletes - Bauer, P.; Kraushaar, L.; Dörr, O.; Bauer, T.; Nef, H.; Hamm, C. W.; Most, A. (European Journal of Applied Physiology, 2020)
Purpose: Low vitamin D levels have been associated with elevated blood pressure (BP) in the general population. However, whether there is an association of vitamin D insufficiency with BP changes during maximum exercise in athletes is currently unclear. Methods: A total of 120 male professional indoor athletes (age 26 ± 5 years) were examined. BP was measured at rest and during a graded cycling test. We assessed the BP response (BPR) during maximum exercise and the respective load. BP and BPR (peak-baseline BP) were analysed with respect to 25-OH vitamin D levels, with levels < 30 ng/mL defining vitamin D insufficiency. Results: 35 athletes were classified as being vitamin D insufficient. BP was not different between sufficient and insufficient vitamin D groups (122 ± 10/75 ± 7 vs. 120 ± 12/77 ± 9 mmHg). At maximum exercise, however, systolic BP (198 ± 17 vs. 189 ± 19, p = 0.026) and the pulse pressure (118 ± 18 vs. 109 ± 21 mmHg, p = 0.021) were higher in the sufficient group; the BPR was not different between groups (76 ± 20/5 ± 6 vs. 69 ± 22/3 ± 6 mmHg, p = 0.103). Athletes with sufficient levels had a higher maximum power output (3.99 ± 0.82 vs. 3.58 ± 0.78 W/kg, p = 0.015) and achieved higher workloads (367 ± 78 vs. 333 ± 80 W, p = 0.003). The workload-adjusted BPR (maximum systolic BP/MPO) was not different between athletes with sufficient and insufficient vitamin D levels (51 ± 10 vs. 56 ± 14 mmHg × kg/W, p = 0.079). Conclusion: Athletes with sufficient vitamin D achieved a higher maximum systolic BP and a higher maximum power output. The workload-adjusted BPR was not different between groups, which suggests that this finding reflects a better performance of athletes with sufficient vitamin D.